2018
DOI: 10.1097/md.0000000000012504
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of platelet to lymphocyte ratio in prostate cancer

Abstract: Background:Recently, the prognostic value of the platelet-to-lymphocyte ratio (PLR) has been identified in multiple cancers. However, the prognostic significance of the PLR in prostate cancer (PCa) remains conflicting. We therefore searched relevant studies and conducted a meta-analysis.Methods:Papers from the databases of PubMed, Web of Science, and the Cochrane Library were retrieved. Six studies comprising 1324 patients were included.Results:The pooled analysis demonstrated that an elevated PLR predicted po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 36 publications
1
42
0
2
Order By: Relevance
“…Conversely, a large patient population study showed that preoperative circulating immune biomarkers such as the NLR and PLR were not associated with postoperative prognosis in black or white men who underwent radical prostatectomy 25 . As to the clinical significance of the PLR in PCa, a high PLR was correlated with poor disease‐free survival and OS, irrespective of ethnicity, tumor stage, and treatment modality 11 . In addition, a past report showed that an increased CRP level is related to PCa risk 26 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Conversely, a large patient population study showed that preoperative circulating immune biomarkers such as the NLR and PLR were not associated with postoperative prognosis in black or white men who underwent radical prostatectomy 25 . As to the clinical significance of the PLR in PCa, a high PLR was correlated with poor disease‐free survival and OS, irrespective of ethnicity, tumor stage, and treatment modality 11 . In addition, a past report showed that an increased CRP level is related to PCa risk 26 .…”
Section: Discussionmentioning
confidence: 98%
“…The prostate‐specific antigen (PSA) test is the most standard diagnostic and prognostic noninvasive marker for PCa but it has the disadvantage of not being a useful prognostic marker in advanced cancer states 8,9 . In recent approaches to investigating PCa prognostic predictors, peripheral inflammatory markers are considered to be among the promising parameters 10,11 . Inflammation is a recognized feature of cancer that contributes substantially to the development and progression of malignant tumors 12‐14 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations